2020
DOI: 10.1111/jcmm.15789
|View full text |Cite
|
Sign up to set email alerts
|

The matricellular protein CCN5 prevents adverse atrial structural and electrical remodelling

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Thus, neutrophils are recruited to the ischemic area and exert potent cytotoxic effects by releasing proteolytic enzymes that affect cardiomyocytes [38]. In this regard, our group has shown in a previous study that CCN5 exhibits anti-inflammatory activity [41,42]. For example, CCN5 knockout mice highly expressed proinflammatory genes in mice with lipotoxic cardiomyopathy [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, neutrophils are recruited to the ischemic area and exert potent cytotoxic effects by releasing proteolytic enzymes that affect cardiomyocytes [38]. In this regard, our group has shown in a previous study that CCN5 exhibits anti-inflammatory activity [41,42]. For example, CCN5 knockout mice highly expressed proinflammatory genes in mice with lipotoxic cardiomyopathy [41].…”
Section: Discussionmentioning
confidence: 99%
“…This involves both enlargement of the atria and fibrosis, adversely affecting atrial conduction and resulting in AF. 7,33 The left atrium is critically involved in both the recurrence and continuation of AF. 34 AF can result in left atrial dilation, which is thought to play a part in structural remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…34 Structural remodeling is also closely linked with fibrosis of the atrium, interfering with normal electrophysiological activity of the myocardium, preventing normal atrial activation, slowing atrial conduction, and leading to disorganized or asynchronous conduction. 7 Fibrosis is associated with increased collagen accumulation, 36 and it has been reported in both animals and humans that such accumulation is caused by AF. 33 A study comparing structural remodeling between AF-affected and healthy horses found elevated collagen deposition in horses with AF, with more marked differences in the left, rather than the right atrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CCN5 may be a potential biomarker for estimating cardiac fibrosis in hypertensive patients. Based on these findings, CCN5 could be a novel therapeutic target that should be developed for stimulating endogenous CCN5 production (Huang et al 2020; Lee et al 2020; Song et al 2022).…”
Section: The Physiological Roles Of Ccn‐family Proteins In Healthy Ti...mentioning
confidence: 99%